Improving Grade 1 Students’ Learning Outcomes in Mathematics Learning on Addition Story Problems Through the UPTD Role Playing Method at SDN 191 BARRU - Adam, Andi; Muhaimin, Nurul; Firmansyah, Firmansyah (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to improve the learning outcomes of first-grade students in mathematics, particularly in solving addition word problems, through the implementation of the role-playing method at UPTD SDN 191 Barru. The research employed a Classroom Action Research (CAR) approach conducted over three cycles, each comprising planning, implementation, observation, and reflection phases. The findings reveal that the role-playing method significantly enhanced students' understanding of addition word problems, with the percentage of students meeting the Minimum Mastery Criteria (MMC) increasing from 60% in the pre-cycle to 96% in the third cycle. Additionally, this method boosted students’ motivation, participation, and ability to relate mathematical concepts to real-life situations. These results suggest that the role-playing method is an effective and engaging strategy for teaching mathematics at the elementary level.